Do Emotions Teach Us How to Teach? Emotional Insights from an International EFL Practicum in Thailand - Rachmawati Nur, Maulidia; Jihan Khalishah, Salsabila; Afandi, Muhajir (VELES Voices of English Language Education Society, 2025)
This qualitative case study explores the emotional geographies experienced by Indonesian pre-service teachers during an international EFL teaching practicum in Southern Thailand. Using Hargreaves’ (2001) framework, which includes moral, sociocultural, political, professional, and physical geographies, this study examines how emotional dynamics influence the practicum experiences of two pre-service teachers over six months. Data were gathered through open-ended questionnaires and semi-structured interviews, then analyzed with Braun and Clarke’s Thematic Content Analysis and the Miles and Huberman model. The findings indicate that three emotional geographies, moral, sociocultural, and political, were most prominent. These emerged through emotional challenges such as managing student behavior, navigating cultural and linguistic differences, and dealing with hierarchical structures that hinder open communication and emotional expression in the classroom. Despite these challenges, participants also experienced emotional growth, increased cultural awareness, and development of their teaching identities. The study highlights the importance of affective experiences in shaping teacher development, particularly within intercultural and multilingual educational settings. It contributes to the expanding body of literature on international teacher education by emphasizing the need to include emotional preparation and intercultural competence in pre-service teacher training. Addressing emotional aspects of teaching through structured reflection, emotional literacy, and mentoring can better prepare future educators for global teaching assignments. The findings suggest that policy and curriculum reforms in teacher education are essential to foster emotional resilience and intercultural adaptation during international practicums.